2018
DOI: 10.1016/j.jhsa.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Location of Osteochondritis Dissecans Lesions of the Capitellum

Abstract: The clock-face localization system allows for precise description of capitellar OCD lesion location, which may facilitate intraoperative decision and longitudinal monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Lesion size and location influence OAT outcomes, with larger and more laterally located lesions considered more severe and difficult to treat [13, 27••, 40, 48, 49, 57]. Johnson et al [5] found roughly 1/3 of capitellar OCD lesions to be laterally located. When comparing 44 laterally located lesions to 43 centrally located lesions, Matsuura and colleagues [27••] found central lesions to fare better in terms of postoperative T&A scores, incidence of radial head subluxation, and RTP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesion size and location influence OAT outcomes, with larger and more laterally located lesions considered more severe and difficult to treat [13, 27••, 40, 48, 49, 57]. Johnson et al [5] found roughly 1/3 of capitellar OCD lesions to be laterally located. When comparing 44 laterally located lesions to 43 centrally located lesions, Matsuura and colleagues [27••] found central lesions to fare better in terms of postoperative T&A scores, incidence of radial head subluxation, and RTP.…”
Section: Resultsmentioning
confidence: 99%
“…The most widely used classifications systems can be found in Table 1 and Table 2. Additionally, Johnson et al [5] recently developed a unique system of lesion localization based on a clock face that intends to more precisely describe lesion location. The intent of this system is to help facilitate intraoperative decision-making and permit longitudinal follow-up for clinical and research purposes.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronal lesion width was also expressed as a percentage of distal humeral articular surface width (Figure 1A), and coronal lesion location was expressed as distance lateral to the trochlear groove (Figure 1B). OCD location on sagittal reconstructions was expressed in degrees relative to the anterior humeral axis, as adapted from Johnson et al 9 (Figure 1C). OCD lesions were also classified according to the International Cartilage Research Society classification and Nelson grade.…”
Section: Methodsmentioning
confidence: 99%
“…(B) Quantification of coronal lesion location as the distance of the center of OCD (dot) lateral to the apex of the humeral trochlear (arrow). (C) Quantification of sagittal lesion location based on method described by Johnson et al 9 A circle of best fit is drawn on the trochlea on the sagittal slice where OCD is largest. The 0° axis is defined as a line starting from the center of the circle running parallel to the anterior humeral line.…”
Section: Methodsmentioning
confidence: 99%